Drivers of integration of green into supplier selections: a systematic literature review. Issue 2 (26th November 2021) - Ograh, Tonny; Ayarkwa, Joshua; Osei-Asibey, Dickson; Acheampong, Alex; Amoah, Peter
Abstract : Purpose: This paper aims to provide a systematic review of extant literature on supplier selection by identifying drivers of integration of Environmental Sustainability (ES) into supplier selection, with the aim of classifying them under broad categories for the development of a framework showing the interrelationships among them. Design/methodology/approach: A search was ran for selected keyword themes using three powerful and rigorous search engines: Scopus, Google Scholar and Science Direct, to identify relevant articles from 12 peer-reviewed journals. These were desk reviewed through manual filtering to select drivers of integration of ES into supplier selection. Findings: Thirty-one drivers identified from 41 relevant articles as propelling integration of ES into supplier selection were then classified into five categories: strong policy direction, high level of commitment, desire for high reputation, robust technology and availability of green products. This yielded a framework showing the interconnectedness among the drivers. Research limitations/implications: The study contributes to the body of knowledge by developing a classification of drivers of integration of ES into supplier selection. The interconnectedness brought to the fore a more subtle appreciation of the drivers of green integration, which could help expand current knowledge outside the narrow scope of isolated drivers. This study provides detailed analyses of drivers of green integration into supplier selection. Originality/value: This paper provides a comprehensive review of drivers of integrating green into supplier selection, which is lacking in the body of knowledge on ES.